2018
DOI: 10.1111/nyas.13963
|View full text |Cite
|
Sign up to set email alerts
|

Global folate status in women of reproductive age: a systematic review with emphasis on methodological issues

Abstract: Inadequate folate status in women of reproductive age (WRA) can lead to adverse health consequences of public health significance, such as megaloblastic anemia (folate deficiency) and an increased risk of neural tube defect (NTD)‐affected pregnancies (folate insufficiency). Our review aims to evaluate current data on folate status of WRA. We queried eight databases and the World Health Organization Micronutrients Database, identifying 45 relevant surveys conducted between 2000 and 2014 in 39 countries. Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 44 publications
1
84
0
3
Order By: Relevance
“…Furthermore, as more human cohort data is generated, or additional clinical studies are performed on DTG, biological interactions and clinical correlations between natural folate intake, folic acid fortified diets, supplemental folate, calcium intake, and resultant DTG, folate, and calcium in blood and serum and should be investigated. It has been previously reported that in human populations where folate fortification is in place, the prevalence of folate deficiency is approximately 0.1% or 1 per 1,000 individuals, but in unfortified population, the base line incidence may be > 20%, 1 in 5, or possibly higher 54 . This 100 to 200-fold difference in the incidence of folate deficiency lowers the average serum folate, increases NTD risk, and may also increase the risk of NTDs associated with early gestational in utero DTG exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as more human cohort data is generated, or additional clinical studies are performed on DTG, biological interactions and clinical correlations between natural folate intake, folic acid fortified diets, supplemental folate, calcium intake, and resultant DTG, folate, and calcium in blood and serum and should be investigated. It has been previously reported that in human populations where folate fortification is in place, the prevalence of folate deficiency is approximately 0.1% or 1 per 1,000 individuals, but in unfortified population, the base line incidence may be > 20%, 1 in 5, or possibly higher 54 . This 100 to 200-fold difference in the incidence of folate deficiency lowers the average serum folate, increases NTD risk, and may also increase the risk of NTDs associated with early gestational in utero DTG exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Some characteristics are as recorded on health service data collections: mother's usual residence, ethnicity, parity, smoking in pregnancy; child's sex, gestational age at birth, birth weight, method of birth. Criteria to define derived variables including maternal age, body mass index (BMI), anaemia before and during pregnancy, insufficient red cell folate levels (folate status less than optimal for women of reproductive age to prevent neural tube defects) and prematurity and birth weight category of the children are detailed in Table S2. Birth weight z‐scores for babies with gestational age of 33 weeks or more, were calculated using the INTERGROWTH‐21ST Neonatal Size Calculator …”
Section: Methodsmentioning
confidence: 99%
“…Для населения, проживающего на территории РФ, характерным является круглогодичный полигиповитаминоз, что обусловлено преобладанием в рационе углеводной пищи и недостаточной культурой употребления овощей и фруктов. По данным Федерального исследовательского центра питания и биотехнологий, повседневный рацион здоровых взрослых людей не обеспечивает адекватное поступление витаминов [16]. Между тем недостаточная обеспеченность организма витаминами рассматривается, с одной стороны, как один из факторов риска развития ряда заболеваний, а с другой, как фактор, который может существенно отягощать течение имеющихся заболеваний.…”
Section: кок с метафолином как источник экзогенного поступления фолатовunclassified
“…Несмотря на использование стратегии фортификации, диверсификации и сапплементации, проблема остается актуальной. Уровень содержания фолиевой кислоты в эритроцитах ниже 906 нмоль/л и 5-МТГФ ниже 748 нмоль/л выявлен более чем у 20% женщин репродуктивного возраста (от 16-18 до 44-49 лет) США и Канады, более чем у 65% женщин Ирландии и Новой Зеландии, более чем у 75% женщин Великобритании и у 100% женщин Швеции [16]. В Германии уровень содержания в эритроцитах фолиевой кислоты выше 906 нмоль/л выявлен только у 9,6% женщин репродуктивного возраста [17].…”
Section: кок с метафолином как источник экзогенного поступления фолатовunclassified